More specifically we will say that g x is the inverse

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: too bad. ( f o g )( x) = f é g ( x )ù ë û é x 2ù =fê + ú ë3 3û æ x 2ö = 3ç + ÷ - 2 è3 3ø = x+2-2 =x Looks like things simplified down considerable here. [Return to Problems] © 2007 Paul Dawkins 195 College Algebra (b) All we need to do here is use the formula so let’s do that. ( g o f ) ( x ) = g é f ( x )ù ë û = g [3x - 2] 1 2 ( 3x - 2 ) + 3 3 22 = x- + 33 =x = So, in this case we get the same answer regardless of the order we did the composition in. [Return to Problems] So, as we’ve seen from this last example it is possible to get the same answer from both compositions on occasion. In fact when the answer from both composition is x, as it is in this case, we know that these two functions are very special functions. In fact, they are so special that we’re going to devote the whole next section to these kinds of functions. So, let’s move onto the next section. © 2007 Paul Dawkins 196 College Algebra Inverse Functions In...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online